Tinjauan Yuridis terhadap Perjanjian Sewa-Menyewa Lahan untuk Operasi Toko Kelontong Berdasarkan Pasal 1548 Kuhperdata - Abdul Hamid Safar; Lucky Dafira Nugroho (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study examines the legal aspects of land lease agreements for Madura grocery stalls based on Article 1548 of the Indonesian Civil Code. A normative juridical method is employed, focusing on statutory regulations and literature review. The primary focus is to identify essential elements in the lease agreement, such as the leased object, mutual consent, and payment obligations. The research also highlights breach of contract issues and emphasizes the importance of legal guarantees in lease relationships. Case studies and recent regulations support the findings, ultimately contributing to legal certainty in land lease practices within the MSME sector.